RDM Based Approach To Solving Decision Making Problem Under Uncertain Environment (International Journal of Innovative Research in Computer Science & Technology, 2024)
The combination of fuzzy logic tools and  multi criteria decision making has a great relevance in  the literature. Real life decision making problem under  uncertainty is usually associated with information that  may be incomplete or imprecise. The information on  which decisions are based is uncertainty . Decision  making theory is based on several type of uncertainty  and tools. Computing with word (CwW) is very effective  tool for decision making. Professor Zadeh the creator of  CwW idea , formulated many challenge problems.  Zadeh’s flight delay problem using  relative-distance-measure is discussed in [1].In this  paper RDM is applied to solve real life decision  making problem. A numerical example is used to  illustrate the procedure of the presented approach.
Keywords: alternatives; decision making; portfolio selection; relative distance measure